1999
DOI: 10.1007/pl00013153
|View full text |Cite
|
Sign up to set email alerts
|

The Long Terminal Repeat of an Endogenous Retrovirus Induces Alternative Splicing and Encodes an Additional Carboxy-Terminal Sequence in the Human Leptin Receptor

Abstract: The evolution of mammalian protein structure and regulation, specifically transcriptional and posttranscriptional regulation, may include among its tools the use of abundant retroviral long terminal repeats (LTRs). In particular, LTRs may be turned into switches for alternative splicing. This type of regulatory pathway is illustrated by the alternative splicing in the human leptin receptor (OBR). The human leptin receptor is involved in the control of important biological processes including energy expenditure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 27 publications
1
39
0
2
Order By: Relevance
“…The insertion of transposable elements in or near introns can result in alternative splicing patterns. Such events are also believed to have contributed to gene evolution (e.g., Kapitonov and Jurka 1999). The insertion of transposable elements into the coding region of genes is typically associated with loss of gene function (Green 1988).…”
Section: Cer Elements May Contribute To C Elegans Gene Structure Andmentioning
confidence: 99%
“…The insertion of transposable elements in or near introns can result in alternative splicing patterns. Such events are also believed to have contributed to gene evolution (e.g., Kapitonov and Jurka 1999). The insertion of transposable elements into the coding region of genes is typically associated with loss of gene function (Green 1988).…”
Section: Cer Elements May Contribute To C Elegans Gene Structure Andmentioning
confidence: 99%
“…HERV-E also appears to be involved in the expression of human pleiotrophin in placenta (12). It has also been demonstrated that a HERV-K LTR encodes the last 67 amino acids of one form of the leptin receptor OBR (13). These findings indicate that an LTR insertion adjacent to or within a gene could have a variety of effects without destroying gene function.…”
mentioning
confidence: 95%
“…Based on the given LTR mutation rate of 0.2-0.3 %, its greater than 15 % difference from other known LTRs suggests that it may be more than 50-75 million-years-old and therefore present in primates and possibly other mammalian annexin A5 genes. The contribution of LTRs as structural mutagens and donors of functional DNA elements for transcription factor binding, such as c-myb [47] or steroids [48], could directly impinge on annexin A5 regulation (Figure 2), although the in i o relevance of specific domains must be assessed under defined conditions. The prospect that human annexin A5 transcription is subject to retroviral repressor element(s) (Figure 3) is a concrete example of symbiotic co-evolution at the molecular level, and a potentially major modulator during cell cycling, tissue differentiation or changed cellular environment.…”
Section: Discussionmentioning
confidence: 99%